2015
DOI: 10.5505/tjtes.2015.69488
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory markers has many Valuable Parameters in the discrimination between acute appendicitis and renal colic

Abstract: BACKGROUND:Only one diagnostic parameter is not available for acute appendicitis. For the establishment of diagnosis, combination of medical history, clinical, laboratory tests, and radiological imaging modalities are used so as to decrease the rates of negative laparotomy and morbidity secondary to delay in diagnosis. Thepresent study aimed to determine haematological and inflammatory markers which will be used in the discrimination of acute appendicitis (AA) and renal colic which are the most frequent and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 11 publications
2
19
2
Order By: Relevance
“…However, (although diagnostic value of RDW in complicated AA has been studied (17,18), Our results did not reveal any difference in RBC between the groups. Consistent with a previous study that included 215 patients and showed that the level of RDW was statistically significantly higher in AA (25), in this study, RDW was found to be an independent diagnostic factor for complicated AA.…”
Section: Discussionsupporting
confidence: 92%
“…However, (although diagnostic value of RDW in complicated AA has been studied (17,18), Our results did not reveal any difference in RBC between the groups. Consistent with a previous study that included 215 patients and showed that the level of RDW was statistically significantly higher in AA (25), in this study, RDW was found to be an independent diagnostic factor for complicated AA.…”
Section: Discussionsupporting
confidence: 92%
“…In parallel to these data, NLR value in our study was lower in flank pain due to urinary stone disease compared to no stone group (2.68 ± 1.86) which was statistically significant. However, our cut-off value was 2.16 and lower than those of Acer et al [6] and Uyeturk et al [27]. Additionally, WBC and PLT results were not statistically significant in the present study.…”
contrasting
confidence: 86%
“…Occlusion of capillaries and venules and finally venous ischemia develop following increased intraluminal pressure with obstruction of the lumen and associated lumen secretions developing in AA. Arterial ischemia finally occurs, and necrosis and perforation result [23,24]. IMA levels rise as a result of this ischemia.…”
Section: Discussionmentioning
confidence: 99%